The effects of mixed infection of strongyles in experimental animals in the Veterinary Research Institute - Md Hakin, Lily Rozita; Panchadcharam, Chandrawathani; Ismail, Erwanas Asmar; Bathmanaban, Premaalatha; Che Mamat, Zaini; Lee, C. H.; Chong, K. L.; Ng, Agnes Wei San; Mohamed, Ramlan (Department of Veterinary Services Malaysia, 2014)
This paper reports the relationship between mixed infections of strongyles with fecal egg count (FEC), packed cell volume (PCV) of the blood and FAMACHA in experimental sheep in VRI. The third larval stage (L3) of strongylid nematode were fed orally to two experimental sheep. Each animal was given 3 ml L3 or equivalent to 3000 larvae. Faecal samples were then collected weekly for a 10 week duration. The FAMACHA scale for anemia estimation was used and blood collection through ear tip was also done twice a week to measure the packed cell volume (PCV) of the blood. The results show that the PCV decreases while faecal egg counts increase over the study period. The FAMACHA scale also increases with time indicating a progressive anemia with the decreasing PCV. As helminth infections are common in small ruminants, the effects of anemia are critical parameters to be monitored in any flock as this will determine its productivity in terms of mortality and morbidity.